2021
DOI: 10.1002/ange.202015298
|View full text |Cite
|
Sign up to set email alerts
|

New Aldehyde‐Functional Methacrylic Water‐Soluble Polymers

Abstract: Aldehyde groups enable facile conjugation to proteins, enzymes, oligonucleotides or fluorescent dyes, yet there are no literature examples of water‐soluble aldehyde‐functional vinyl monomers. We report the synthesis of a new hydrophilic cis‐diol‐based methacrylic monomer (GEO5MA) by transesterification of isopropylideneglycerol penta(ethylene glycol) using methyl methacrylate followed by acetone deprotection via acid hydrolysis. The corresponding water‐soluble aldehyde monomer, AGEO5MA, is prepared by aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 49 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…A PGEO5MA 34 (or GO 34 ) precursor was first synthesized via RAFT solution polymerization of GEO5MA in ethanol at 70 °C using a non-ionic trithiocarbonate chain transfer agent, following a similar experimental protocol to that previously reported by our group (Scheme S2). 32,33 A final GEO5MA conversion of 86% was achieved after 180 min, as determined by 1 H NMR analysis in CD 3 OD. End-group analysis of the purified PGEO5MA homopolymer using the same technique indicated a mean degree of polymerization (DP) of 34 (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A PGEO5MA 34 (or GO 34 ) precursor was first synthesized via RAFT solution polymerization of GEO5MA in ethanol at 70 °C using a non-ionic trithiocarbonate chain transfer agent, following a similar experimental protocol to that previously reported by our group (Scheme S2). 32,33 A final GEO5MA conversion of 86% was achieved after 180 min, as determined by 1 H NMR analysis in CD 3 OD. End-group analysis of the purified PGEO5MA homopolymer using the same technique indicated a mean degree of polymerization (DP) of 34 (Figure S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, comparing the C 1s XPS data obtained for the PGEO5MA and PAGEO5MA brushes revealed a shift in the ratio of the O−C�O, C�O, C−O−C/C−O−H, and C−H peaks that is consistent with brush oxidation (Figure S14). 36 Recently, we have reported that PAGEO5MA-based chains, 32 diblock copolymer nano-objects, 33,35 and brushes 36 can be further functionalized with various amino acids, such as L-histidine, via reductive amination. For surface-grafted PAGEO5MA brushes, this involves immersion into an aqueous solution containing the desired amine reagent and sodium cyanoborohydride (NaBH 3 CN), prior to heating to 50 °C for 24 h. Herein, this protocol was adapted to functionalize PAGEO5MA brushes using a hydrophilic diamine (Jeffamine EDR-148) to prepare the corresponding PDAGEO5MA brushes, as illustrated in Scheme 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations